2008
DOI: 10.1128/aac.00020-08
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping as a Tool for Antibiotic Resistance Surveillance of Neisseria gonorrhoeae in New Caledonia: Evidence of a Novel Genotype Associated with Reduced Penicillin Susceptibility

Abstract: Antibiotic resistance in Neisseria gonorrhoeae continues to be a major concern in public health. Resistance of N. gonorrhoeae bacteria to penicillin G is widespread in most developed countries, which has necessitated a change to newer drugs for treatment of gonococcal infections. Recent reports indicate that resistance to these newer drugs is increasing, highlighting the need for accurate therapeutic recommendations. In some countries or communities, however, N. gonorrhoeae isolates are still susceptible to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This assay tested two adjacent SNPs (PorB 120/121), giving a WT result if there was a WT sequence in both positions or a SNP result if there was variation in at least one position. It is possible that only a specific amino acid change contributes to increased MICs to ESCs at this locus (22)(23)(24). In addition, previous studies have shown that porB mutations do not affect ESC susceptibility in the absence of the mtrR Ϫ35del SNP (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…This assay tested two adjacent SNPs (PorB 120/121), giving a WT result if there was a WT sequence in both positions or a SNP result if there was variation in at least one position. It is possible that only a specific amino acid change contributes to increased MICs to ESCs at this locus (22)(23)(24). In addition, previous studies have shown that porB mutations do not affect ESC susceptibility in the absence of the mtrR Ϫ35del SNP (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Our assay clearly detects all mutated QRDRs and allows the identification of common genotypes, whether the QRDRs contain single or double mutations, providing valuable epidemiological tools. When this method is used in conjunction with similar assays and in vitro analyses, essential antibiotic resistance surveillance can be performed for public health purposes.Gonorrhea rates generally remain high in New Caledonia and Oceania, where penicillins are the recommended treatment (17,19,22). Increasing penicillin resistance means that fluoroquinolones are the next therapeutic option, but monitoring of relevant antibiotics for effectiveness for public health purposes (2,7,15,16,23) is required.…”
mentioning
confidence: 99%
“…Gonorrhea rates generally remain high in New Caledonia and Oceania, where penicillins are the recommended treatment (17,19,22). Increasing penicillin resistance means that fluoroquinolones are the next therapeutic option, but monitoring of relevant antibiotics for effectiveness for public health purposes (2,7,15,16,23) is required.…”
mentioning
confidence: 99%
“…Molecular tools are being used to provide an understanding of the genetic basis of resistance as well as to supplement phenotypic antimicrobial susceptibility testing (9,15,16,20,22,23,24). These tools have not yet advanced to a stage where they can be used in place of phenotypic testing, mainly because the genetic determinants of resistance to most antibiotics are not yet fully known.…”
mentioning
confidence: 99%
“…These tools have not yet advanced to a stage where they can be used in place of phenotypic testing, mainly because the genetic determinants of resistance to most antibiotics are not yet fully known. Nevertheless, for well-characterized resistance mechanisms, molecular tools offer an accurate and objective means of detection and systems for the detection of pivotal resistance determinants for public health purposes when viable isolates are not required have been described (22,23).…”
mentioning
confidence: 99%